Studies on effect of process parameters variation on bio-oil yield in subcritical and supercritical hydrothermal liquefaction of malaysian oil palm biomass - Chan, Y.H. (Springer International Publishing, 2015)
Experimental studies on liquefaction of three types of Malaysian oil palm biomass, namely empty fruit bunch (EFB), palm mesocarp fiber (PMF) and palm kernel shell (PKS) using water at subcritical and supercritical conditions are conducted in an Inconel batch reactor. The main objective of the present study is to investigate the effect of variation in process parameters such as temperature, pressure and reaction time on the bio-oil yield from the hydrothermal liquefaction of the biomass feedstocks. At the end of the chapter, a general life cycle assessment (LCA) of a liquefaction process is conducted to evaluate the impacts on the environment. In the present study, it is found that the optimum temperature and pressure for maximum bio-oil yield for all the three biomass feedstocks is at supercritical condition of water (390Â°C, 25MPa) and the optimum reaction time is 2h for EFB and PMF and 4h for PKS. The LCA indicates that liquefaction process has the highest influence in global warming potential, while other impacts such as acidification, eutrophication, toxicity and photo-oxidant formation are negligible. Â© Springer International Publishing Switzerland 2015.